Comparative diagnostic pharmacology : - Coyne, Cody Paul (Blackwell Publishing, 2006)
Comparative Diagnostic Pharmacology: Clinical and Research Applications in Living-System Models is the first evidence-based reference text devoted exclusively to the subject of applying pharmaceutical and biopharmaceutical agents as diagnostic probes in clinical medicine and investigative research.This unique and groundbreaking book is a versatile guide for clinicians and researchers interested in using pharmacologic agents to: diagnose disease, assess physiological processes...